2014
DOI: 10.1080/07448481.2014.917653
|View full text |Cite
|
Sign up to set email alerts
|

Impediments to Academic Performance of Bisexual College Students

Abstract: Given the unique impediments for bisexual students, college health professionals should consider specifically addressing needs for bisexual students, bisexual women in particular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 28 publications
0
9
0
4
Order By: Relevance
“…On the other hand, a 2011 survey 11 of 28 US colleges of veterinary medicine revealed that > 20% of LGBTQ+ students heard homophobic comments occasionally to very frequently at school. This study did not evaluate effects on mental health or academic outcomes; however, findings from other studies [29][30][31][32] suggest that exposure to harassment and discrimination hinders the academic performance of LGBTQ+ students.…”
mentioning
confidence: 92%
“…On the other hand, a 2011 survey 11 of 28 US colleges of veterinary medicine revealed that > 20% of LGBTQ+ students heard homophobic comments occasionally to very frequently at school. This study did not evaluate effects on mental health or academic outcomes; however, findings from other studies [29][30][31][32] suggest that exposure to harassment and discrimination hinders the academic performance of LGBTQ+ students.…”
mentioning
confidence: 92%
“…Le modèle du stress associé a `un statut de minorité sexuelle (stress minoritaire; Meyer, 2003) propose en ce sens que les individus dont l'identification, les attirances ou les comportements sexuels seraient non conformes a `la norme hétérosexuelle seraient exposés a `des expériences de stigmatisation, de discrimination ou de victimisation, lesquelles influenceraient a `la hausse l'incidence des difficultés d'adaptation vécues par ces jeunes (Hatzenbuehler, 2009). Il a été révélé que ces expériences de stress minoritaire, encore bien présentes au postsecondaire même si moins généralisées qu'au secondaire (Chamberland, Émond, Julien, Otis & Ryan, 2011), ont un effet délétère non seulement sur le rendement scolaire des jeunes de minorités sexuelles (Klein & Dudley, 2014;Woodford & Kulick, 2015), mais également sur leur santé mentale (Parra, Benibgui, Helm & Hastings, 2016). En ce qui concerne les individus en discordance d'une part, les auteurs mentionnent, par exemple, que ceux qui s'identifient hétérosexuels et qui rapportent des attirances ou des comportements avec des personnes de même sexe tendent a `ne pas intégrer les communautés de la diversité sexuelle et risquent donc d'être privés d'un réseau de soutien (Pathela et al, 2006).…”
Section: L'âge Adulte éMergent Une Période D'exploration Identitaireunclassified
“…The Meyer (1995) minority stress model, widely used to understand various social factors that influence health in minority populations, posits that stigma and discrimination in society influence the health and mental health of SGM. Multiple minority stressors such as homo/bi/trans-phobic prejudice and stigma, victimization, internalized homo/bi/trans-phobia, and hiding one's sexual or gender identity, have been found to have adverse effects on the health and mental health of SGM populations (Klein & Dudley, 2014;Lehavot & Simoni, 2011). However, Meyer (2003) acknowledges that the minority stress model fails to differentiate between differing realities that fall under the SGM banner.…”
Section: Background and Significancementioning
confidence: 99%